Factors predictive of long-term visual outcomes of Group D eyes treated with chemoreduction and low-dose IMRT salvage: The Children's Hospital Los Angeles experience. Issue 8 (26th March 2014) - Berry, Jesse L; Jubran, Rima; Wong, Kenneth; Lee, Thomas C; Murphree, A Linn; Kim, Jonathan W
Abstract : Aim: To evaluate clinical factors predictive of visual outcomes in Group D retinoblastoma eyes. Methods: Retrospective chart review of patients with Group D retinoblastoma from January 2000 to December 2009. All patients were treated with systemic chemoreduction and external beam radiation as salvage therapy when indicated. Primary outcome measure was visual acuity. Clinical factors evaluated include quadrants of subretinal fluid, extent of vitreous seeding, involvement of more/less than 50% of the macula, endophytic/exophytic tumour classification, and presence of tumour behind the lens at diagnosis. Results: Fifty-two Group D eyes of 41 patients were included; 10 eyes with visual acuity better than 20/80, 32 eyes with vision worse than 20/100 and 10 eyes with indeterminate vision (fix and follow). Complete retinal detachment (p=0.002), involvement of >50% of the macula (p=0.01), and seeding >3 quadrants (p=0.05) were associated with worse visual outcome. Average follow-up was 50.0 months (range: 10–118 months). Conclusions: At presentation, it is difficult to predict which Group D eyes will be salvaged with useful vision following systemic chemotherapy. The presence of complete retinal detachment, macular involvement and extensive seeding on presentation were factors associated with a worse visual prognosis in this study. These findings can guide the ophthalmologist in clinical decision making, as well as in counselling parents.